2015
DOI: 10.1136/bmj.h3163
|View full text |Cite
|
Sign up to set email alerts
|

Generic immunosuppression in solid organ transplantation: systematic review and meta-analysis

Abstract: ObjeCtiveTo compare the clinical efficacy and bioequivalence of generic immunosuppressive drugs in patients with solid organ transplants.Design Systematic review and meta-analysis of all studies comparing generic with innovator immunosuppressive drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
61
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(66 citation statements)
references
References 68 publications
4
61
1
Order By: Relevance
“…Doubts were raised in the literature regarding clinical equivalence of generic drugs after substitution versus their brand-name counterpart in several therapeutic fields. [7][8][9][10][11][12][13][14][15][16][17] A recent meta-analysis including studies of generic and brandname cardiovascular drugs did not show a significant difference in terms of safety or tolerability between the 2 types of drug. 18 However, a systematic review of editorials addressing generic drug substitution in cardiology depicted a majority of negative views on clinical equivalence.…”
Section: Leclerc Et Al Generics Commercialization and Adverse Eventsmentioning
confidence: 99%
“…Doubts were raised in the literature regarding clinical equivalence of generic drugs after substitution versus their brand-name counterpart in several therapeutic fields. [7][8][9][10][11][12][13][14][15][16][17] A recent meta-analysis including studies of generic and brandname cardiovascular drugs did not show a significant difference in terms of safety or tolerability between the 2 types of drug. 18 However, a systematic review of editorials addressing generic drug substitution in cardiology depicted a majority of negative views on clinical equivalence.…”
Section: Leclerc Et Al Generics Commercialization and Adverse Eventsmentioning
confidence: 99%
“…150 Another potential source of tacrolimus variability is conversion to generic formulations; however, the evidence is scarce and of low quality. 151 Bioequivalence between generic tacrolimus and its innovator has been demonstrated in healthy volunteers and kidney transplant recipients. In the subgroup of kidney transplant patients older than 60 years caution is needed as 1 randomized study showed bioequivalence standards were not met by generic tacrolimus.…”
Section: Highly Modifiable Contributors To Variabilitymentioning
confidence: 99%
“…Uncontrolled switching, particularly between generic formulations, should be avoided. 151,154 The conversion from twice-daily to prolonged-release tacrolimus (capsules), both in kidney and liver transplant recipients, leads to lower blood trough concentrations and a reduced IPVof tacrolimus. 155,156 In a single study performed in liver transplant recipients, the early conversion to prolonged-release tacrolimus capsules was accompanied by a significant reduction of TCMR rates.…”
Section: Highly Modifiable Contributors To Variabilitymentioning
confidence: 99%
“…[94][95][96] Adults with weakened immune systems are particularly vulnerable to infection and the burden of transmissible disease is heavier than that in immunocompetent patients because infections recur, persist longer and are often more severe than usual. [94][95][96] Recurrent infections can place "frequent flier" patients at hospitals at greater risk of further contracting hospital-acquired infections.…”
Section: Tick-borne Encephalitis (Tbe) Vaccinationmentioning
confidence: 99%
“…[94][95][96] Adults with weakened immune systems are particularly vulnerable to infection and the burden of transmissible disease is heavier than that in immunocompetent patients because infections recur, persist longer and are often more severe than usual. [94][95][96] Recurrent infections can place "frequent flier" patients at hospitals at greater risk of further contracting hospital-acquired infections. 97 The list of conditions that can cause relevant immunocompromise include: primary immunodeficiencies; malignancy, particularly in patients undergoing treatment; human immunodeficiency virus (HIV) infection; iatrogenic immunosuppression for organ transplantation; rheumatologic disorders; and autoimmune diseases.…”
Section: Tick-borne Encephalitis (Tbe) Vaccinationmentioning
confidence: 99%